In Vivo Assessment of Bone Enhancement in the Case of 3D-Printed Implants Functionalized with Lithium-Doped Biological-Derived Hydroxyapatite Coatings: A Preliminary Study on Rabbits - OKTAR, FAİK NÜZHET (MDPI, 2020)
We report on biological-derived hydroxyapatite (HA, of animal bone origin) doped with lithium carbonate (Li-C) and phosphate (Li-P) coatings synthesized by pulsed laser deposition (PLD) onto Ti6Al4V implants, fabricated by the additive manufacturing (AM) technique. After being previously validated by in vitro cytotoxicity tests, the Li-C and Li-P coatings synthesized onto 3D Ti implants were preliminarily investigated in vivo, by insertion into rabbits' femoral condyles. The in vivo experimental model for testing the extraction force of 3D metallic implants was used for this study. After four and nine weeks of implantation, all structures were mechanically removed from bones, by tensile pull-out tests, and coatings' surfaces were investigated by scanning electron microscopy. The inferred values of the extraction force corresponding to functionalized 3D implants were compared with controls. The obtained results demonstrated significant and highly significant improvement of functionalized implants' attachment to bone (p-values <= 0.05 and <= 0.00001), with respect to controls. The correct placement and a good integration of all 3D-printed Ti implants into the surrounding bone was demonstrated by performing computed tomography scans. This is the first report in the dedicated literature on the in vivo assessment of Li-C and Li-P coatings synthesized by PLD onto Ti implants fabricated by the AM technique. Their improved mechanical characteristics, along with a low fabrication cost from natural, sustainable resources, should recommend lithium-doped biological-derived materials as viable substitutes of synthetic HA for the fabrication of a new generation of metallic implant coatings.
Keywords: biological-derived hydroxyapatite coatings; lithium doping; food industrial by-products; in vivo extraction force; pulsed laser deposition; 3D printing; MAGNESIUM-ENRICHED HYDROXYAPATITE; THIN-FILMS; METALLIC IMPLANTS; GENE-EXPRESSION; PORCINE BONE; STEM-CELLS; DIFFERENTIATION; DEPOSITION